Instant Powder Formulation for Anti Anemia and Optimization Exctraction Condition of Moringa pterygosperma Gaertn Leaves Using MAE - Anggraeni, Yosita; Jufri, Mahdi Jufri; Munim, Abdul (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X)
Iron supplement containing ferrous sulfate is commonly used for anaemia. Unfortunately, it has bad taste, can cause nausea, and made adverse effects if taken in large doses for long periods. It is necessary to ????ind an alternative source of raw materials, including those from plants. Moringa pterigospera Gaertn leaves was selected because it contains iron and other nutritions. The purpose of this work was to make instant powder formula for anti anaemia using Moringa leaves extract as an alternative for ferous suphate iron suplementation. The extraction was performed by Microwave Assisted Extraction method. Optimization of extraction condition was performed by creating some variations in solvent composition (0- 70% ethanol), microwave power (450 to 900 watts) and extraction time (3 to10 min). Iron content was determined by Atomic Absorption Spectrophotometer at wave length of 248 nm. Instant powder formula was made in 3 concentrations of sodium CMC as suspending agent. Results of the study showed that the most optimal extraction condition which resulted the highest iron content (2.4 mg/g extracts) achieved with 900 watts microwave power, 10 min extraction time and aqua demineralisata. According to 30 panelists of hedonic test, formula which used 5% w/w of sodium CMC got the highest scores. Its powder form had 2.31% of loss on drying and 7.74 g/sec of ????low rate for powder form and pH of 5.78, viscosity of 15.98 cps for reconstituted form.